2015
DOI: 10.1590/1981-6723.4914
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of chicken nuggets with partial replacement of meat and fat by pea fibre

Abstract: The aim of this study was to develop and evaluate a chicken nugget formulation with partial substitution of the meat or fat by pea fibre. Three formulations were developed: Control (C) – commercial formulation, Fibre Less Meat (FLM) – reduction of 10% of meat and addition of 2% of pea fibre and Fibre Less Fat (FLF) – reduction of 10% of fat and addition of 2% pea fibre. The products were characterized for their pH value, instrumental colour, texture, cooking loss (frying), proximate composition, and sensory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 23 publications
5
26
1
4
Order By: Relevance
“…Similar results were found by Alves et al (2016) when they replaced pork back fat with pork skin and green banana flour gel in a bologna type sausage and in which the replacement of 20% to 100% of the fat significantly increased the moisture of this product compared to the control batch. By replacing 10% chicken fat with 2% pea fiber with 8% water in nuggets of chicken, Polizer et al (2015) observed an increase in the value of moisture compered to control treatment.…”
Section: Proximate Composition and Total Calories Contentmentioning
confidence: 95%
“…Similar results were found by Alves et al (2016) when they replaced pork back fat with pork skin and green banana flour gel in a bologna type sausage and in which the replacement of 20% to 100% of the fat significantly increased the moisture of this product compared to the control batch. By replacing 10% chicken fat with 2% pea fiber with 8% water in nuggets of chicken, Polizer et al (2015) observed an increase in the value of moisture compered to control treatment.…”
Section: Proximate Composition and Total Calories Contentmentioning
confidence: 95%
“…The percentage of cooking loss and shrinkage were determined according to the methods established by Polizer et al (2015). The percentage of cooking loss was calculated as follows:…”
Section: Cooking Loss and Reduced Size (Shrinkage)mentioning
confidence: 99%
“…Regarding the composition of nugget formulations (Table 1) the control formulation (NC) had lower moisture content (38.26 g/100g) than the NF12 formulation, probably due to the water retention capacity of fiber components. Polizer et al (2015) also found increased moisture content (51.69 g/100g) in nuggets produced with addition of pea fiber partially replacing meat and fat. The addition of FPP to nugget formulations increased the ashes content, especially in formulation NF12 (2.74 g/100g).…”
Section: Physicochemical Characterizationmentioning
confidence: 77%
“…In relation to cooking properties, the weight loss was determined according to Polizer et al (2015), being calculated as percentage using the Equation. 1.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%